States, Social Knowledge, and the Origins of Modern Social Policies - Rueschemeyer, Dietrich (Book collections on Project MUSE., 2017)
From the 1850s to the 1920s, laws regulating the industrial labor process, pensions for the elderly, unemployment insurance, and measures to educate and ensure the welfare of children were enacted in many industrializing capitalist nations. This same period saw the development of modern social sciences. The eight essays collected here examine the reciprocal influence of social policy and academic research in comparative context, ranging across policy areas and encompassing developments in Britain, the United States, Germany, France, Canada, Scandinavia, and Japan. Introduced by the editors, the essays include Part I on the emergence of modern social knowledge by Ira Katznelson, Anson Rabinbach, and Björn Wittrock and Peter Wagner; Part II on reformist social scientists and public policymaking by Dietrich Rueschemeyer and Ronan Van Rossem, Libby Schweber, and John R. Sutton; Part III on state managers and the uses of social knowledge by Stein Kuhnle and Sheldon Garon, and a conclusion by Rueschemeyer and Theda Skocpol. Originally published in 1995. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.